STUDI FITOKIMIA Ocimum spp.: KOMPONEN KIMIA MINYAK ATSIRI KEMANGI DAN RUKU-RUKU - Sulianti, Sri Budi (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Isolation of essential oils of two species of Ocimum (kemangi and ruku-ruku) were done by hydrodistilation. The chemical composition of those essential oils were analysed by GC-MS. Totaly 38 chemical components of kemangi essential oil were identified, and six of them are the major chemical constituents, ie. ethyl hexadecanoic acid (17.72 %), ethyl octadecanoic acid (14.83 %), ethyl 9-octadecenoic acid (10.62 %), methyl eugenol (4.88 %), Z-citral (7.02 %) and geranial (7.86 %), On the other hand, the essential oil of ruku-ruku contain 31 components with the main five major chemical components, i.e. ethyl hexadecanoic acid (19.33 %), ethyl octadecanoic acid (15.39 %), ethyl 9-octadecenoic acid (11.30 %), methyl eugenol (8.69%) and zerumbona (4.76 %).